2016
DOI: 10.5194/acp-16-2109-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric OH reactivity in central London: observations, model predictions and estimates of in situ ozone production

Abstract: Abstract. Near-continuous measurements of hydroxyl radical (OH) reactivity in the urban background atmosphere of central London during the summer of 2012 are presented. OH reactivity behaviour is seen to be broadly dependent on air mass origin, with the highest reactivity and the most pronounced diurnal profile observed when air had passed over central London to the east, prior to measurement. Averaged over the entire observation period of 26 days, OH reactivity peaked at ∼ 27 s −1 in the morning, with a minim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 27 publications
12
95
2
Order By: Relevance
“…Yoshino et al (2006) found a good correlation between missing reactivity and measured oxygenated VOCs (OVOCs) in three seasons, except for winter, assuming that the unmeasured OVOCs could be major contributors of missing reactivity; in one case, the OVOCs could increase reactivity by over 50 % (Lou et al, 2010). The observation-based model (OBM) was widely used to evaluate the measured reactivity (Lee et al, 2010;Lou et al, 2010;Whalley et al, 2016), confirming the important contribution from OVOCs and undetected intermediate compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshino et al (2006) found a good correlation between missing reactivity and measured oxygenated VOCs (OVOCs) in three seasons, except for winter, assuming that the unmeasured OVOCs could be major contributors of missing reactivity; in one case, the OVOCs could increase reactivity by over 50 % (Lou et al, 2010). The observation-based model (OBM) was widely used to evaluate the measured reactivity (Lee et al, 2010;Lou et al, 2010;Whalley et al, 2016), confirming the important contribution from OVOCs and undetected intermediate compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Nashville, USA (SOS) 11.0 3.8 (Kovacs et al, 2003) New York, USA (PMTACS-NY2001) 18.8 0.7 (Ren et al, 2003a(Ren et al, , 2003b New York, USA (PMTACS-NY2004) 25.1 4.0 (Ren et al, 2006a) Mexico City, Mexico (MCMA-2003) 47.5 14.3 (Shirley et al, 2006) Houston, USA (TexAQS) 9.4 0.4 (Mao et al, 2010) Houston, USA (TRAMP2006) 12.24 0.03 (Mao et al, 2010) Paris, France (MEGAPOLI) 40.3 22.8 (Dolgorouky et al, 2012) Lille, France 7.4 0 (Hansen et al, 2015) London, UK (ClearfLo) 18.1 5.9 2.7 † (Whalley et al, 2016) Remote Michigan, USA (Prophet2000) 7.8 2.6 (Di Carlo et al, 2004) Hyytiälä, Finland (BFORM) 8.6 3.9 (Sinha et al, 2010) Hyytiälä, Finland (HUMPPA-COPEC2010) 11.5 8.9 (Nölscher et al, 2012) Rocky Mountains, USA (BEACHON-SRM08) 6.7 2.1 (Nakashima et al, 2014) Michigan, USA (CABINEX) 11.6 6.3 (Hansen et al, 2014) Amazon, Brazil (ATTO) dry season 49.6 35.8 …”
Section: Urbanmentioning
confidence: 99%
“…15 In an attempt to account for the additional OH reactivity potentially arising from unmeasured oxidation intermediates, a number of studies invoked box modelling to determine the abundance of these species and their contribution to kOH. These efforts have been met with mixed results: while some managed to reconcile the total kOH with the sum of reactivities once the oxidation intermediates were taken into account (Whalley et al, 2016), others obtained different degrees of improvement on the agreement between the two, leaving different fractions of kOH still unaccounted for (Edwards et al, 2013;Elshorbany et al, 20 2012;Kaiser et al, 2016;Kovacs et al, 2003;Lee et al, 2009;Lou et al, 2010;Mao et al, 2012;Mogensen et al, 2011;Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The total OH reactivity values of measured VOCs in Berlin (2.6 s −1 ) are similar to the average total OH reactivity from VOCs observed in other European cities, such as Paris (approximately 4.0 s −1 ) and London (1.8 s −1 ) (Dolgorouky et al, 2012;Whalley et al, 2016), and, not surprisingly, lower than those observed at cities in the Pearl River Delta region of China (8-14 s −1 ). Specifically, Liu et al (2008) reported OH reactivity from a measurement campaign in Ghangzhou and Xinken during 1 month in the autumn of 2004.…”
Section: Oh Reactivitymentioning
confidence: 57%
“…The GRIMM 5.416, a condensation particle counter with n-butanol, provided total PN count over a size range from 4 to 3000 nm at a flow rate of 1.5 L min −1 , and the uncertainty for 1 min sampling was ± 0.1 % or ± 15 cm −3 (Helsper et al, 2008;Wiedensohler et al, 2017). The GRIMM 5.403, a scanning mobility particle sizer equipped with a long DMA combined with a CPC with n-butanol, measured PN concentrations with size distribution information for particles between 10 and 1100 nm at a sample flow rate of 0.3 L min −1 and a sheath flow rate of 3 L min −1 .…”
Section: Particle Number Concentration and Surface Area Measurementsmentioning
confidence: 99%